The effect of receivables turnover, inventory turnover and current ratio on profitability - Yusup, Wahyu Ersandi; Hariani, Swarmilah (Jurnal Riset Manajemen dan Bisnis, 2023)
Manufacturing companies in the food and beverage sub-sector in 2015-2019 show corporate profit figures that fluctuate yearly. With this phenomenon, companies must strive to increase profits through cost management and know the factors that significantly influence the level of Return On Assets. This study aims to determine the effect of Accounts Receivable Turnover, Inventory Turnover, and Current Ratio on Return on Assets. The population of the food and beverage sub-sector companies listed on the Indonesia Stock Exchange 2015-2019 is 130, with a sample of 70 using a purposive sampling technique. This study uses quantitative causal analysis. The results of this study indicate that Accounts Receivable Turnover (X1) and Inventory Turnover (X2) has a significant negative effect. In contrast, the Current Ratio (X3) significantly positively affects Return on Assets.